A 2-Year Integrated Agriculture and Nutrition Program Targeted to Mothers of Young Children in Burkina Faso Reduces Underweight among Mothers and Increases Their Empowerment: A Cluster-Randomized Controlled Trial. Issue 5 (13th April 2016) - Olney, Deanna K; Bliznashka, Lilia; Pedehombga, Abdoulaye; Dillon, Andrew; Ruel, Marie T; Heckert, Jessica
Abstract: Background: Recent evidence demonstrates the benefits of integrated agriculture and nutrition programs for children's health and nutrition outcomes. These programs may also improve mothers' nutrition and empowerment outcomes. However, evidence from rigorous evaluations is scarce. Objective: We examined impacts of Helen Keller International's 2-y enhanced-homestead food production (E-HFP) program in Burkina Faso on the secondary impact measures of mothers' nutrition and empowerment. Methods: We used a cluster-randomized controlled trial whereby 55 villages with 1767 mothers of young children were randomly assigned to 3 groups: 1 ) control, 2 ) E-HFP with the behavior change communication (BCC) strategy implemented by older women leaders, or 3 ) E-HFP with BCC implemented by health committee members. Data for the treatment groups were pooled for this analysis because no differences were found between the 2 groups in key mothers' outcomes. We used difference-in-differences (DID) estimates to assess impacts on mothers' dietary intake, diversity, body mass index (BMI; in kg/m 2 ), prevalence of underweight (BMI <18.5), and empowerment. Results: The E-HFP program significantly increased mothers' intake of fruit (DID = 15.8 percentage points; P = 0.02) and marginally increased their intake of meat/poultry (DID = 7.5 percentage points; P = 0.08) and dietary diversity (DID = 0.3 points; P = 0.08). The prevalence of underweight was significantly reduced among mothers in treatment compared with control villages by 8.7 percentage points ( P < 0.01). Although the changes in BMI did not differ between mothers in treatment and control villages, there was a marginally significant interaction (baseline underweight × change in BMI; P -interaction = 0.07), indicating that underweight mothers had a greater increase in BMI than did mothers who were not underweight. The E-HFP program also positively affected mothers' overall empowerment score (DID = 3.13 points out of 37 possible points; P < 0.01) and 3 components of empowerment: meeting with women (DID = 1.21 points out of 5 possible points; P < 0.01), purchasing decisions (DID = 0.86 points out of 8 possible points; P = 0.01), and health care decisions (DID = 0.24 points out of 2 possible points; P = 0.05). Conclusions: Helen Keller International's E-HFP program in Burkina Faso substantially improved mothers' nutrition and empowerment outcomes. These positive impacts benefit the mothers themselves and may also improve their ability to care for their children. This trial was registered at clinicaltrials.gov as NCT01825226.